Analysis of Interest Rates, Exchange Rupees, and Inflation During and After The Global Financial Crisis In Indonesia 2002-2011 - Oktarianda Putra; Yusbar Yusuf; Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study discusses the analysis of the Interest Rate, Exchange Rate and Inflation in Indonesia in 2002-2011. Data analysis using descriptive analysis, the analysis compares the data with various theories that support and are explained. Description of the results of this study are: (1) The interest rate, exchange rate, and inflation before the economic crisis inIndonesia in 2002-2011, (2) interest rate, exchange rate, and inflation when the monetary crisis in Indonesia in 2002-2011,and (3) the interest rate, exchange rate, and inflation after the global financial crisis in Indonesia in 2002-2011. The purpose of this study was to describe the level of interest rates, exchange rate, and inflation in Indonesia in 2002-2011.The results of this study indicate that ( 1 ) Prior to the global financial crisis interest rates in 2002-2007 Indonesia has decreased significantly , from 14.56 % to 8.00 % , the exchange rate tends to fluctuate , which in 2002 was 9,500 while in 2006 was 11,500 , and in 2007 was 10,100 , and inflation in Indonesia tend to fluctuate, which in 2002 was 4.46 while in2007 was 6.6 and in 2007 was 7.4 . ( 2 ) When the global financial crisis interest rate in 2008 was 9.25 % while in the year 2009 was 6.50 % . , The exchange rate tends to decrease , which in 2008 was 9,500 while in 2009 was 9,200 , and inflation in Indonesia in 2008 was 11.1 while in 2009 was 2.8 tends to decline . ( 3 ) After the global financial crisis interest ratestend to decline in 2010 was 6.50%, while in the year 2011 was 6.00 % , the exchange rate in 2010 was 9,700 while in 2011 was 9,500 , and inflation in Indonesia in 2008 was 11.1 while in 2009 was 2.8 .Keywords: analysis, interest rate, exchange rate, and inflation.